The Bank of Albania Building: Memory and Modernization - Nepravishta, Florian (ICONARCH International Congress of Architecture and Planning, 2017)
The paper examines the adaptive re-use and restoration project of the Bank of Albania building in Tirana, an Italian architecture heritage. Analysis of the intervention has more to do with the notion of dynamic change in the concept of preserving the memory of architectural heritage. It analyzes how this change is managed specifically by architects who redesign this building that today is part of the Albanian architectural heritage. The paper provides some answers to the questions: Was the intervention necessary? Can we accept the interventions as a positive influence? How the architects have managed it? What is done to ensure the preservation of esthetics and cultural heritage values? In the end, is concluded that after having followed the way of respecting and preserving the inherent values of the building the project results were successful. The intervention that realizes the best use of the historic buildings sometimes is the only way to care properly and preserve the architectural heritage.